Cytokinin-Deficient Transgenic Arabidopsis Plants Show Multiple Developmental Alterations Indicating Opposite Functions of Cytokinins in the Regulation of Shoot and Root Meristem Activity - Werner, Tomáš (American Society of Plant Biologists, 2003)
Cytokinins are hormones that regulate cell division and development. As a result of a lack of specific mutants and biochemical tools, it has not been possible to study the consequences of cytokinin deficiency. Cytokinin-deficient plants are expected to yield information about processes in which cytokinins are limiting and that, therefore, they might regulate. We have engineered transgenic Arabidopsis plants that overexpress individually six different members of the cytokinin oxidase/dehydrogenase (AtCKX) gene family and have undertaken a detailed phenotypic analysis. Transgenic plants had increased cytokinin breakdown (30 to 45% of wild-type cytokinin content) and reduced expression of the cytokinin reporter gene ARR5:GUS (β-glucuronidase). Cytokinin deficiency resulted in diminished activity of the vegetative and floral shoot apical meristems and leaf primordia, indicating an absolute requirement for the hormone. By contrast, cytokinins are negative regulators of root growth and lateral root formation. We show that the increased growth of the primary root is linked to an enhanced meristematic cell number, suggesting that cytokinins control the exit of cells from the root meristem. Different AtCKX-green fluorescent protein fusion proteins were localized to the vacuoles or the endoplasmic reticulum and possibly to the extracellular space, indicating that subcellular compartmentation plays an important role in cytokinin biology. Analyses of promoter:GUS fusion genes showed differential expression of AtCKX genes during plant development, the activity being confined predominantly to zones of active growth. Our results are consistent with the hypothesis that cytokinins have central, but opposite, regulatory functions in root and shoot meristems and indicate that a fine-tuned control of catabolism plays an important role in ensuring the proper regulation of cytokinin functions.